Role of ERK-MAPK signaling pathway in pentagastrin-regulated growth of large intestinal carcinoma - Mao, Jia-Ding (Baishideng Publishing Group Inc, 2014)
AIM: To explore the role and mechanisms of extracellular signal-regulated protein kinase-mitogen-activated protein kinase (ERK-MAPK) signaling in pentagastrin-regulated growth of large intestinal carcinoma. METHODS: HT-29 cells were incubated in different media and divided into the control group, pentagastrin group, proglumide group, and pentagastrin + proglumide group. No reagent was added to the control group, and other groups were incubated with reagent at different concentrations. Changes in proliferation of HT-29 cells were detected by MTT assay, and the optimal concentrations of pentagastrin and proglumide were determined. The changes in proliferation index (PI) and apoptosis rate (AR) of HT-29 cells were detected by Annexin V-fluorescein isothiocyanate flow cytometry. mRNA expression of pentagastrin receptor/cholecystokinin-B receptor (CCK-BR), ERK1/2 and K-ras were detected by reverse transcriptase polymerase chain reaction. The protein and phosphorylation level of ERK1/2 and K-ras were detected by western blotting. All data were analyzed by analysis of variance and SNK-q test. RESULTS: The proliferation of HT-29 cells was stimulated by pentagastrin at a concentration of 6.25-100 mg/L, and the optimal concentration of pentagastrin was 25.0 mg/L (F = 31.36, P < 0.05). Proglumide had no obvious effect on the proliferation of HT-29 cells, while it significantly inhibited the proliferation of HT-29 cells stimulated by pentagastrin when the concentration of proglumide was 8.0-128.0 mg/L, and the optimal concentration was 32.0 mg/L (F = 24.31, P < 0.05). The PI of the pentagastrin (25.0 mg/L) group was 37.5% ± 5.2%, which was significantly higher than 27.7% ± 5.0% of the control group and 27.3% ± 5.8% of the pentagastrin (25.0 mg/L) + proglumide (32.0 mg/L) group (Q = 4.56-4.75, P < 0.05). The AR of the pentagastrin (25.0 mg/L) group was 1.9% ± 0.4%, which was significantly lower than 2.5% ± 0.4% of the control group and 2.4% ± 0.3% of the pentagastrin (25.0 mg/L) + proglumide (32.0 mg/L) group (Q = 4.23-4.06, P < 0.05). mRNA expression of CCK-BR was detected in HT-29 cells. The phosphorylation levels of ERK1/2 protein and phosphorylated K-ras protein of the pentagastrin group were 0.43% ± 0.04% and 0.45% ± 0.06%, which were significantly higher than 0.32% ± 0.02% and 0.31% ± 0.05% of the control group (Q = 7.78-4.95, P < 0.05), and 0.36% ± 0.01% and 0.35% ± 0.04% of the pentagastrin + proglumide group (Q = 5.72-4.08, P < 0.05). There were no significant differences in the mRNA and protein expression of ERK1/2 and K-ras among the control, pentagastrin, proglumide and pentagastrin + proglumide groups (F = 0.52, 0.72, 0.78, 0.28; P > 0.05). CONCLUSION: Gastrin stimulates proliferation of HT-29 cells and inhibits apoptosis by upregulating phosphorylation of ERK and K-ras through the Ras-Raf-MEK1/2-ERK1/2 pathway, and this is restrained by proglumide.